The Effectiveness of the Role of Satintelkam Through Collaboration with PSHT and PSHW Silat Colleges to Create Conducive Kamtibmas in the Jurisdiction of the Madiun City Police - Maula, Bagas Dyas (Advances in Police Science Research Journal, 2024)
Indonesia is known as a plural country that has a variety of cultures, one of which is pencak silat. The rise of conflicts involving pencak silat that occur in Indonesia has become a national issue. Especially the conflict betweet PSHT and PSHW that occurred in Madiun City. The conflict was caused by several factors, one of which was high fanaticism and differences in understanding of the history of the martial arts organization. This research used the field research method with a qualitative approach. In this case, the author tries to describe the role of the Madiun City Police Satintelkam in raising PSHT and PSHW and describe the effectiveness of the implementation of the mobilization. Based on these references, the author tries to analyze and draw conclusions to be used as evaluation material for the performance of the National Police in the future.